The Knowledge Enhancement of Al Huda MTS Students about The Use, Storage and Disposal of Animal Medicine through Educational Seminars and Demonstration - Aryani, Dhita Evi; Herawati, Herawati; Oktavianie, Dyah Ayu; Permata, Fajar Shodiq (Faculty of Veterinary Medicine Universitas Brawijaya, 2020)
Currently, there are many pet shops, animal clinics, and animal lover communities in Malang. Data from UB's animal education hospitals showed an increasing number of patients visiting there. This reflects that the owner had considered his favorite animal as part of his family that must be treated if they are sick. Drugs medicine plays an important role in the treatment of animal diseases. Therefore, pet owners must know how to use and store drugs properly so that the efficacy of the drug does not change, and the results of treatment are achieved. When the drug is not used anymore, the owner must know how to properly dispose of the drug to prevent the drug from being mixed, polluting the environment, or even being used by irresponsible people. The aim of this community service was to provide additional knowledge about how to use, store and dispose of veterinary medicines. The theme we took was